Inclusive Rehabilitation Process Ensuring the Best Outcome for Post Injury Intervention – A Social Security Perspective - Aziz Mohammed, Mohammed Azman; Darus, Azlan; Hussain, Hafez (Malaysian Journal of Medical Sciences, 2026)
Injuries remain a significant contributor to disability and economic burden globally and in Malaysia. Traditional models of care often position rehabilitation as a late-stage intervention, limiting functional recovery and return-to-work outcomes. This paper presents a social security-driven approach to rehabilitation, drawing on the experience of the Social Security Organisation of Malaysia (PERKESO). Emphasis is placed on early intervention, integrated case management, investment in advanced rehabilitation technologies, and sustainable financing mechanisms. Evidence from PERKESO’s rehabilitation approaches, infrastructure and disability management processes demonstrate improved reintegration outcomes and functional recovery. This model highlights the importance of embedding rehabilitation across the continuum of care to optimise outcomes and strengthen workforce productivity.